The Image of Historical Figures in Teodor Jeske-Choiński’s Revolutionary Trilogy (on the Example of Camille Desmoulins, Georges Danton and Maximilien Robespierre) - Sojak, Małgorzata (Contrasts in humanities: literature, language, culture, 2023)
In the revolutionary trilogy, Jeske-Choiński uses historical figures to present the cruelties of the events of the end of the 18th century. For this reason, the fictional characters become a background for the actions of historical heroes, whose profiles, in turn, are presented by the author by means of suggesting their moral evaluation. Although it seems coherent – the characters are just as cruel as the world they live in – it makes the reader feel uneasy about the contrast between the historical facts and the characters in the novel. In this work, the representations of historical figures created by Jeske-Choiński will be compared with their real counterparts, described by historians.